Optimization of Large-Scale Growable ATM Switching FabricsDOI: 10.14209/jcis.1994.5 - Jajszczyk, Andrzej; Roszkiewlcz, Michal (Journal of Communication and Information Systems, 2015)
Large switching fabrics are frequently obtained by arranging elementary switches in various ways. Growability of such structures is of the great importance. This paper presents results of our investigations on how switching elements should be initially arranged to minimize the fabric cost expressed by the number of elementary switches, and further how does the optimum structure behave in the growth process. In our investigations we have used the dynamic programming method, which is based on Bellman's optimality principle. We assumed the Clos-like architecture of the switching fabric with some modifications which are necessary due to the differences between arrangements of circuitswitched and ATM fabrics. As the result, the comparison of the cost of ATM switching fabrics composed of typical 8 x 8 and 16 x 16 elementary switches is given.